Deposit Base of Commercial Banks of Uzbekistan: Modern Status and Ways to Strengthen - Juraev Isroil Ibrohimovich (Universitas Muhammadiyah Sidoarjo, 2019)
The article analyzes the current state of deposit operations of commercial banks in our country and examines the level of maturity of deposit operations before reaching the conclusion and providing recommendations on strengthening deposit base.